Les aspects épidémiologiques, cliniques et biologiques du surpoids et de l’obésité chez les patients hospitalisés en médecine interne - RABOUH FATNA (Université Amar Telidji de Laghouat Faculté de Médecine, 2021)
The objective of this study is to determine the prevalence of obesity and overweight subjects in the EPH-Laghouat internal medicine department and to describe its epidemiological, clinical and biological aspects in addition to determining the risk factors of obesity. This within the framework of an epidemiological investigation 72 people aged from 16 to 88 years were questioned and examined in the service of internal medicine. In the second part we did a physical examination comprising for 72 subjects: weight, height, blood pressure and measurement of body composition using bioelectrical impedance; a food survey; a balance sheet of total energy intake as well as carbohydrate and lipid intake. These subjects responded to an interview and questionnaire regarding personal history, background and family history as well. A biochemical assessment is carried out in certain subjects. The prevalence of overweight and obesity in our representative sample is in the order of 26.39% and 22.23% respectively. Our study found that BMI is very highly correlated with gender, age and urbanized background; however it is not correlated with income level. It depends also on the profession; there is a very highly significant difference between the BMI values. The highest prevalence of obesity has been observed among the unemployed, retirees, and administrative workers. We found in this study a significant link between arterial hypertension in the subject or in a family member and BMI greater than 25. The unhealthy lifestyle of the obese people which is hyperlipidic, normoprotidic and hyperglycemic type with low fluid intake. In addition unjustified prescription of corticosteroids is considered also to be a reason of gaining weight. In our series we observed a predominance of the android type in both sexes. There is a strong correlation between percentage of body fat and BMI. Sedentary lifestyle and lack of physical activity play a very important role in weight gain. Dietary factors and physical activity are believed to be the main modifiable factors in obesity and overweight.
121 p.